Implementation of a practical antibiotic policy in the Czech Republic - Kolár, M; Látal, T (Infection control and hospital epidemiology, 1999)
We describe the antibiotic control policy at the Faculty Hospital in Olomouc, Czech Republic. Practical examples of successful implementation of the policy are provided.
Keywords: Drug Utilization; zdravotní politika; Health Policy; spotřeba léčiv; Anti-Bacterial Agents; kontrola infekce; Humans; Czech Republic; Infection Control; lidé; antibakteriální látky; Česká republika